Lack of a clinically relevant effect of sugammadex on anti-Xa activity or activated partial thromboplastin time following pretreatment with either unfractionated or low-molecular-weight heparin in healthy subjects - De Kam, Pieter-Jan; Kruithof, Annelieke C; van Lierop, Marie-José; Moerland, Matthijs; Dennie, Justin; Troyer, Matthew D; Langdon, Ronald B; Gutstein, David E; Burggraaf, Jacobus; El Galta, Rachid (International journal of clinical pharmacology and therapeutics, 2014)
To investigate the potential effect of sugammadex on anti-Xa anticoagulantactivity of enoxaparin and the activated partial thromboplastin time (APTT) of unfractionated heparin (UFH). This two-part, randomized, double-blind, placebocontrolled, four-period cross-over study was performed in healthy males (18 - 45 years). In each period, subjects received 40 mg enoxaparin (in part 1), 5,000 units UFH (in part 2), or placebo followed by 4 or 16 mg/kg sugammadex, or placebo. Treatments were separated by ≥ 4 days. Primary endpoints were anti-Xa activity and APTT both time-averaged from 3 to 30 minutes post-dose. Geometric mean ratios (GMRs) and their two-sided 90% confidence limits were calculated for anticoagulant plus sugammadex (4 or 16 mg/kg) vs. anticoagulant plus placebo. The pre-specified threshold for a potential effect of clinical relevance was a 90% upper confidence limit (UCL) > 1.50. In part 1 (n = 13), the 90% UCLs were 1.07 and 1.08 for GMRs of anti-Xa activity after dosing with 4 and 16 mg/kg sugammadex, respectively. In part 2 (n = 43), the 90% UCLs for GMRs of APTT were 1.06 and 1.15. Neither sugammadex dose produced a treatment effect that met the pre-specified criterion for potential clinical relevance. Treatments were generally well tolerated. In healthy subjects, treatment with 4 mg/kg and 16 mg/kg sugammadex did not change either anti-Xa activity or APTT to a clinically meaningful extent following pretreatments with enoxaparin or UFH.